Evaluation of Financial Reporting to Assess the Economic Performance of the Central Tapanuli Regional Government - Purba, Sahala; Ginting, Arie Tymoty R.; Barus, Yudi Andeska; Surbakti, Yohanes Arlenta; Ginting, Bremanta (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This analysis aims to investigate the performance efficiency of the Central Tapanuli County government using eight fiscal ratios, including regional fiscal independence, regional fiscal dependence, degree of fiscal decentralization, PAD effectiveness, PAD efficiency, and local taxes. Efficiency, local tax efficiency, and contribution BUMD. This study is a quantitative descriptive analysis from 2013 to 2022. Evaluate existing data on financial ratios using documentation techniques for data collection. The evaluation results showed regional independence at 7.14%, a normal level included in the participation relationship pattern, regional financial dependence at a low level of 17.02%, fiscal decentralization reserve ratio at a shallow level of 17.01%, and PAD effectiveness ratio. Very effective inclusion 0.88%, very efficient inclusion PAD efficiency 0.77%, inefficient inclusion regional tax efficiency 3.16%, less efficient inclusion regional tax efficiency 33%, BUMD contribution level very high. Looking at the evaluation results, it can be concluded that the performance of Central Tapanuli Regency between 2013 and 2022 was ineffective in regional development.